A method of profile control applied in laser technology - Tran Thi Nhung; Nguyen Trong Khuyen; Nguyen Hoang Tien (Journal of Military Science and Technology, 2025)
The proposed model allows the generation of any two-dimensional profile, which can be applied, for example, in laser welding and cutting techniques. In the paper, a system model for generating two-dimensional profiles using two galvanometer mirrors placed on two perpendicular axes is studied and designed. The forward and inverse kinematic equations establishing the relationship between the mirror motion and the laser profile are proposed and thoroughly solved by the author, and the author also presents the control problem to generate the desired profile. Simulations on Matlab are performed for circular and figure-8 profiles. The simulation results obtained profiles similar to the desired profile, both in shape and scanning frequency.